Rivers of Light—Ternary Exciplex Blends for High Efficiency Solution‐Processed Red Phosphorescent Organic Light Emitting Diodes. (11th November 2021) - Saghaei, Jaber; Russell, Steven M.; Jin, Hui; Burn, Paul L.; Pivrikas, Almantas; Shaw, Paul E.
Abstract: Red‐emitting organic light‐emitting diodes (OLEDs) are important for displays and lighting, with the latter benefiting from solution processable materials, which would enable low embedded energy, scalable fabrication. Herein, the effect of annealing and phase separation on the performance of solution‐processed OLEDs incorporating a light‐emitting layer composed of the exciplex host, m‐MTDATA:OXD‐7, and a red phosphorescent light‐emitting dendrimer, Ir(tDC pq)3, is described. Solution‐processed OLEDs containing an annealed emissive layer with a low dendrimer concentration (2 wt%) are found to have the best performance, which is higher than the device in which the light‐emitting layer is not annealed. The improvement in the performance of the annealed device is ascribed to improved charge mobility within the emissive layer caused by phase separation of the OXD‐7. The OLEDs containing annealed m‐MTDATA:OXD‐7:(2 wt%) Ir(tDC pq)3 have maximum current, power, and external quantum efficiencies of 17.9 cd A −1, 19.4 lm W −1, and 14.8 ± 0.6%,  respectively. The fact that the maximum external quantum efficiency (EQE) of 14.8% is larger than that expected based on the photoluminescence quantum yield (PLQY) and the normal out‐coupling efficiency of 20% from a bottom‐emitting device is determined to arise from the different pathways of exciton formation under photoexcitation and charge injection. Abstract : Thermally driven phase separation is found to improve the performance of solution‐processed organic light‐emitting diodes with an exciplex host:red phosphorescent light‐emitting dendrimer emissive layer blend. The phase separated devices containing 2 wt% of the phosphorescent dendrimer are found to have maximum current, power, and external quantum efficiencies of 17.9 cd A −1, 19.4 lm W −1, and 14.8 ± 0.6%, respectively.